‘Keeping Faith’: An Exploration of Welsh Muslim Identity - Gilliat-Ray, Sophie (Islam and Christian-Muslim relations, 2021)
This article contributes to research about Muslim communities in Wales by exploring some of the ways in which Muslims identify with Wales and have brought their faith and traditions into conversation with Welsh cultural, religious and civic life. This occurs through strategic use of the Welsh language, especially on occasions that ‘celebrate the nation’, recognition and identification with features of the landscape and geography of Wales, and the continuity of leadership of Muslim communities. In addition, the vibrancy of Welsh Muslim institutions suggests that they have a significant role to play in the contemporary religious landscape of Wales. I suggest that they are responsible for sustaining some of the characteristic features of historic Welsh religious culture, in a context where the main denominations of the Christian churches are struggling to maintain active congregations. The energy and activism of Welsh Muslims suggests that they are taking on some responsibility for ‘keeping faith’ in Wales and creating new post-secular spaces and practices in the urban public sphere that engage in a dialogical and reflexive relationship with aspects of Welsh tradition.